Decision-making in mania: a PET study. - Rubinsztein, J; Fletcher, P; Rogers, R; Ho, L; Aigbirhio, F; Paykel, E; Robbins, T; Sahakian, B (2001)
Poor decision-making is often observed clinically in the manic syndrome. In normal volunteers, decision-making has been associated with activation in the ventral prefrontal cortex and the anterior cingulate gyrus. The aim of this study was to evaluate task-related activation in bipolar manic patients in these regions of the prefrontal cortex using PET. Six subjects with mania, 10 controls and six subjects with unipolar depression (an affective patient control group) were scanned using the bolus H(2)(15)O method while they were performing a decision-making task. Activations associated with the decision-making task were observed at two levels of difficulty. Task-related activation was increased in the manic patients compared with the control patients in the left dorsal anterior cingulate [Brodmann area (BA) 32] but decreased in the right frontal polar region (BA 10). In addition, controls showed greater task-related activation in the inferior frontal gyrus (BA 47) than manic patients. A positive correlation (r(s) = 0.88) between task-related activation in the anterior cingulate and increasing severity of manic symptoms was found. Depressed patients did not show significant task-related differences in activation compared with control subjects in the regions of interest. In conclusion, these patterns of activation point to abnormal task-related responses in specific frontal regions in manic patients. Moreover, they are consistent with neuropsychological observations in patients with lesions in the ventromedial prefrontal cortex, who show similar difficulties with decision-making and provide early evidence for context-specific neural correlates of mania.